THE IMPLEMENTATION OF CURRICULUM 2013: THE PREPARATION AND THE TEACHING LEARNING PROCESS IN THE CLASSROOM OF SMP NEGERI 2 SEPAUK (A DESCRIPTIVE STUDY ON SMPN 2 SEPAUK) - Utomo, Abet Yudho; Regina, Regina; Sudarsono, Sudarsono (JOEEL (Journal of English Education and Literature), 2021)
This research was aimed to describe the use of curriculum 2013 at the SMP Negeri 2 Sepauk, Sintang. It started from the preparation until the process of the teaching and learning process. This study discussed about the implementation of the curriculum, difficulty, and how to overcome the difficulty in teaching and learning using curriculum 2013. The subjects of this study are the English teachers, the principle, the vice principle of curriculum, and the seventh grade students. Furthermore, the writer used interview also observation checklist as the tools in obtaining the data. As the result, the implementation of curriculum 2013 has not been running as it supposed to be. The result of this study is expected to be informative to many educators such as teacher, reader, or students which are correlated with English Educational system and give a good image of the schools condition in using curriculum 2013.